2016
DOI: 10.1118/1.4941014
|View full text |Cite
|
Sign up to set email alerts
|

Vision 20/20: Magnetic resonance imaging‐guided attenuation correction in PET/MRI: Challenges, solutions, and opportunities

Abstract: Attenuation correction is an essential component of the long chain of data correction techniques required to achieve the full potential of quantitative positron emission tomography (PET) imaging. The development of combined PET/magnetic resonance imaging (MRI) systems mandated the widespread interest in developing novel strategies for deriving accurate attenuation maps with the aim to improve the quantitative accuracy of these emerging hybrid imaging systems. The attenuation map in PET/MRI should ideally be de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
148
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 130 publications
(153 citation statements)
references
References 193 publications
(260 reference statements)
0
148
0
Order By: Relevance
“…Burgos et al (2014 ) demonstrated superior performance of atlas-based methods in CT synthesis and PET quantitative accuracy compared to a segmentation method using an UTE MRI sequence in brain imaging. Likewise, Mehranian et al (2016 ) demonstrated that atlas-based methods provide the most accurate attenuation maps compared to simultaneous activity-attenuation estimation and state-of-the-art 3-class segmentation method. In whole-body imaging, Hofmann et al (2011 ) proposed an atlas-based method combined with a pattern recognition technique, which resulted in less than 10% uptake error on average, thus outperforming standard segmentation methods in whole-body imaging.…”
Section: E-mail Address: Habibzaidi@hcugech (H Zaidi)mentioning
confidence: 99%
See 1 more Smart Citation
“…Burgos et al (2014 ) demonstrated superior performance of atlas-based methods in CT synthesis and PET quantitative accuracy compared to a segmentation method using an UTE MRI sequence in brain imaging. Likewise, Mehranian et al (2016 ) demonstrated that atlas-based methods provide the most accurate attenuation maps compared to simultaneous activity-attenuation estimation and state-of-the-art 3-class segmentation method. In whole-body imaging, Hofmann et al (2011 ) proposed an atlas-based method combined with a pattern recognition technique, which resulted in less than 10% uptake error on average, thus outperforming standard segmentation methods in whole-body imaging.…”
Section: E-mail Address: Habibzaidi@hcugech (H Zaidi)mentioning
confidence: 99%
“…Beside the precious anatomical information provided by CT or MRI, additional information that can be extracted from these images, such as attenuation properties of body tissues and motion information can be exploited for correction of emission data and quantitative PET image reconstruction. However, MRIguided attenuation correction in whole-body PET/MRI proved to be a challenging issue and has therefore remained an active and open research question during the last decade ( Mehranian et al, 2016 ). Commercially available PET/MR scanners employ tissue classification methods, which rely on segmentation of MR images into tissue classes and assigning uniform linear attenuation coefficients to each tissue class ( Martinez-Moller et al, 2009 ;Arabi et al, 2015 ).…”
Section: E-mail Address: Habibzaidi@hcugech (H Zaidi)mentioning
confidence: 99%
“…The bulk of quantitative PET/MRI research to date focused on addressing the challenges of MRI-guided PET attenuation correction. Three categories of MRI-guided attenuation correction techniques have emerged [66]. This includes (1) segmentation-based approaches, which segment MR images into different tissue classes and assign predefined attenuation coefficients to each class, (2) atlas-based and machine learning techniques in which co-registered MR-CT Atlas pairs are used to derive a pseudo-CT image or to learn a mapping function that predicts the pseudo-CT from actual patient's MRI, and (3) the recently revisited joint emission and attenuation reconstruction algorithms or maximum likelihood reconstruction of attenuation and activity (MLAA), in which the attenuation map is estimated from emission or transmission data.…”
Section: Reliability Of Suv Measurements In Pet/mrimentioning
confidence: 99%
“…An additional complexity arises from the attenuation and scattering of annihilation photons by objects present in the field of view, which may also induce SUV underestimation if not accounted for. This includes patient's bed, MRI radiofrequency body or surface coils, and patient positioning aids [66]. Transmission or CT scanning-based predetermination of attenuation maps for rigid objects (bed, body coils, etc.)…”
Section: Reliability Of Suv Measurements In Pet/mrimentioning
confidence: 99%
“…The quantitative analysis using clinical whole-body studies showed that the proposed MLAA-AC method resulted in − 10.2% quantification error in bony structures compared to − 18.4% induced by the 4-class MRAC method. For a more detailed survey of the strategies devised to address the challenges of AC in PET/MRI, interested readers are referred to recent reviews on the topic (Mehranian et al, 2016, Bezrukov et al, 2013.…”
Section: Introductionmentioning
confidence: 99%